2022
DOI: 10.1155/2022/2782112
|View full text |Cite
|
Sign up to set email alerts
|

Kui Jie Tong Ameliorates Ulcerative Colitis by Regulating Gut Microbiota and NLRP3/Caspase-1 Classical Pyroptosis Signaling Pathway

Abstract: Ulcerative colitis (UC) is one of the most refractory digestive diseases in the world. Kui jie tong (KJT) is an effective traditional Chinese medicine used clinically to treat UC. This study observed the regulatory effects of KJT on NIMA-related kinase 7- (NEK7-) activated nod-like receptor protein-3 (NLRP3)/caspase-1 classical pyroptosis pathway and intestinal flora in UC model rats. KJT components were analyzed using an ultraperformance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS). A UC Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…As shown in Figures11 and 12, IL-17A, B, C, E, and F can bind to Act1/TRAF3IP2 and TRAF6 through diferent IL-17 receptors (IL-17RA, B, C, and E) and further regulate AP-1(Fos/Jun) to promote the release of proinfammatory cytokines and chemokines. DSS can induce colitis in mice[51][52][53] and rats[54][55][56]. Te expressions of Act1/TRAF6/FOS/JUN of the IL-17 signaling pathway in Caco-2 cells were increased after being stimulated with DSS in our experiment.…”
supporting
confidence: 48%
“…As shown in Figures11 and 12, IL-17A, B, C, E, and F can bind to Act1/TRAF3IP2 and TRAF6 through diferent IL-17 receptors (IL-17RA, B, C, and E) and further regulate AP-1(Fos/Jun) to promote the release of proinfammatory cytokines and chemokines. DSS can induce colitis in mice[51][52][53] and rats[54][55][56]. Te expressions of Act1/TRAF6/FOS/JUN of the IL-17 signaling pathway in Caco-2 cells were increased after being stimulated with DSS in our experiment.…”
supporting
confidence: 48%
“…We also dug deeper into the changes of GM at the genus level and expect to screen out specific microorganisms potentially responsible for the efficacy of AVO. The increased Turicibacter had been observed in many UC individuals, and Turicibacter was positively associated with inflammation ( 24 , 25 ). In our study, Turicibacter was conspicuously increased after the DSS challenge, and oral AVO decreased Turicibacter which has been increased by DSS.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3/ caspase-1 signaling pathway is a classical signaling pathway for pyroptosis (Burdette et al, 2021). Shigui Xue et al found that inhibition of the NLRP3/caspase-1 pathway was an effective way to improve DSS rats (Xue et al, 2022), which was supported by data from Hu et al (2021). The NLRP3/caspase-1 pathway exerts a vital role in UC by regulating pyroptosis.…”
Section: Introductionmentioning
confidence: 91%